Hemolytic effects of a football-specific training session in elite female players - Tan, D.; Dawson, B.; Peeling, P. (International Journal of Sports Physiology and Performance, 2012)
Purpose: This study aimed to quantify the hemolytic responses of elite female football (soccer) players during a typical weekly training session. Methods: Ten elite female football players (7 field players [FPs] and 3 goalkeepers [GKs]) were recruited from the Australian National Women`s Premier League and asked to provide a venous blood sample 30 min before and at the immediate conclusion of a typical weekly training session. During this training session, the players` movement patterns were monitored via a 5-Hz global positioning system. The blood samples collected during the training session were analyzed for iron status via serum ferritin (SF) analysis, and the hemolytic response to training, via serum free hemoglobin (Hb) and haptoglobin (Hp) measurement. Results: 50% of the participants screened were found to have a compromised iron stores (SF P = .011), and the serum Hp levels were significantly decreased (P = .005), with no significant differences recorded between the FPs and GKs. However, the overall distance covered and the movement speed were significantly greater in the FPs. Conclusions: The increases in free Hb and decreases in Hp levels provide evidence that a typical team-sport training session may result in significant hemolysis. This hemolysis may primarily be a result of running-based movements in FPs and/or the plyometric movements in GKs, such as diving and tackling.